Pelatihan Penyusunan Soal AKM bagi Guru PJOK di Kabupaten Banyuwangi - Nurhayati, Faridha (PADIMAS Jurnal Pengabdian Masyarakat, 2024)
The implementation of the Minimum Competency Assessment (AKM) in all subjects is still not fully understood by teachers regarding how to appropriate questions. This was experienced by physical education teachers in the Banyuwangi Regency area, understanding regarding AKM was still lacking and many experienced difficulties developing AKM questions based on reading literacy and numeracy for physical education subjects. The conditions experienced by these partners require alternative solutions, namely through training to increase teachers' insight and skills regarding AKM and how to prepare questions that are appropriate for physical education subjects. This PKM program aims to improve the understanding and skills of physical education teachers in preparing AKM questions. The target for implementing PKM activities is the physical education teachers in Banyuwangi Regency. The activity was carried out on October 6 and was attended by 11 physical education teachers. Carrying out activities in the form of training and evaluating the activities that have been implemented. Based on the results of filling out the response questionnaire, this training is very important to carry out and the results of the teacher's response to the activities carried out are in the very good category, both in terms of material and facilitators.